THE ANALYZE OF HEMATOLOGICAL PARAMETERS OF ELITE WOMEN TAEKWONDOERS BEFORE AND AFTER TRAINING - Yalcin Kaya; Sakir Bezci (Pamukkale University, 2010)
This scientific research aimed to explain the hematological parameters effects of acute training period for youths both sportswomen who will attend the World Teakwondo Championship. This research is based on the blood samples which taken, maximal were training before and after of the period require applied on the sportswomen. According to these, in terms of sportswomen before and after training there is significant increase in WBC, HGB, PLT (P<0.01) RBC HCT and MCH (P<0.05) levels and insignificant differences (P<0.05) in MCV and MCHC levels. The dependent 't' test was applied to determine the differences before and after the training. To conclude, since the results of the data are in the normal limits, there is no risk for sportswomen. However, since it is possible to find important evidences related with human health and performance due to the environmental and individual parameters, it is recommended that regular researches should be done.